2019
DOI: 10.1007/s11414-019-09685-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Attendance to the Emergency Department after Release from Prison: a Prospective Data Linkage Study

Abstract: The aim of this paper was to identify characteristics and predictors of frequent emergency department (ED) use among people released from prisons in Queensland, Australia. Baseline interview data from a sample of sentenced adults were linked to ED and hospital records. The association between baseline characteristics and frequent ED attendance was modelled by fitting multivariate logistic regression models. Participants who had ≥ 4 visits to the ED in any 365-day period of community follow-up were defined as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…HCU in recently released prisoners is elevated [5,6,[11][12][13][14] and often associated with previous psychiatric conditions [15,16]. Despite these findings during prisoners' incarceration and soon after their release, knowledge of long-term HCU in people who have been in prison is scant.…”
Section: Introductionmentioning
confidence: 99%
“…HCU in recently released prisoners is elevated [5,6,[11][12][13][14] and often associated with previous psychiatric conditions [15,16]. Despite these findings during prisoners' incarceration and soon after their release, knowledge of long-term HCU in people who have been in prison is scant.…”
Section: Introductionmentioning
confidence: 99%
“…Around 40% of those interviewed by the research team reported that they had received therapy or counseling in the 3 months since release which reinforces that individuals are receiving mental health services independent to those provided by community mental health teams. The mental health needs of those exiting prison are clearly high; rates of emergency department attendance are elevated in this group ( 26 ), as are inpatient hospital admissions ( 27 ). However, those with mental health difficulties and criminal justice involvement commonly experience difficulties in obtaining mental health care in the community, often due to the stigma associated with their offending behavior ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important among people with co-occurring serious mental illness and substance use; 18 a particularly vulnerable population who experience high levels of poor health and social outcomes post release from prison. [19][20][21] Preventing imprisonment among people with co-occurring mental illness and substance use may also be achieved through diversion to appropriate mental health services at various points prior to, and when moving through the criminal justice system. 22,23 Holistically addressing pertinent social factors via mental health services, such as housing instability, 24,25 may also reduce offending and prevent entry into secure custodial settings.…”
Section: Discussionmentioning
confidence: 99%